Study on the use and quality of documentary information from the Internet according to students at the National University, Costa Rica: Case study laboratory room Biblioteca Joaquín García Monge - Garrido Cordero, Irina (2007)
It is no secret that computer services came to revolutionize the world. More than a service, have since become an indispensable tool for humanity, because they simplify and make life easier in many of his orders, through its various support options. These advances are added Internet services, so that by the mid 1980's assessed the need for such a research tool in order to apply it in various fields of human knowledge.This research, based on the use and quality of documentary information from the Internet, with application to the students of the Universidad Nacional, Costa Rica, if the Library Board Laboratory Joaquin Garcia Monge, develops in the form of theses.